In vitro recovery of diploid embryos in banana - Neves, Tárcia dos Santos; Silva, Sebastião de Oliveira e; Oliveira, Roberto Pedroso de (Pesquisa Agropecuaria Brasileira, 2001)
This study aimed to evaluate the recovery technique applied to zygotic embryos of banana diploid genotypes and to examine the effect of defective embryo and endosperm on in vitro germination. Genotypes Calcutta, Butuhan, Malaccensis, França, 0304-02, 1304-06, 4252-04 and 9379-09 were used. One hundred seeds of each genotype were collected and soaked in distilled water for 24 hours. They were then disinfected by solutions of 0.5% silver nitrate followed by 5% sodium chloride. Excised embryos were put in MS medium with 30 g L-1 sucrose and 7 g L-1 agar and cultured in growth chambers under dark and 26 ± 20C. Germination occurred between the 5th and the 20th day of growth, being 53.25% in average after 45 days independently of the genotype. Wild species showed a higher germination frequency as compared to that of the hybrid genotypes, and normal embryos and endosperm were not essential for the in vitro germination.